A review of emergency obstetric care services and obstetric fistula in North Western Nigeria / Tukur Ismail - Tukur, Ismail (2017)
Confinement is a life-changing, pleasant and joyful event and experience for many mothers. It is a period of difficulty and sadness for some women and her immediate families, particularly when it is accompanied by serious illness, debilitating injuries and death of the baby, mother or both. About half a million women die yearly from causes related to pregnancy and delivery. For each maternal death, approximately 10 to 15 other women sustain serious morbidity, including obstetric fistula (OF) which is closely associated to overall maternal morbidity and mortality. The most effective approach to reducing OF occurrence is to provide essential obstetric services at the community level with prompt access to emergency obstetric services at the first referral level. This study examined the availability of Emergency obstetric care (EmOC) services and factors that influenced the utilisation of the services and identified the potential risk factors of obstetric fistula among women in Nigeria. Quantitative and qualitative methods were used. A community survey involving 60 women and 40 men was conducted in five political wards in Gusau, Zamfara State, Nigeria. Data were collected from March to April 2013 using semi-structured validated questionnaires. For qualitative component, a focus group discussions (FGDs) and Key Informant Interviews (KIIs) were employed. FGD sessions were conducted separately for eight married women and for four men. KIIs were conducted with four sampled traditional birth attendants and six health personnel (nurses) involved in emergency obstetric care services from three selected facilities. A case–control study with a sample of 200 (ratio of 1 case: 1 control) was conducted from August to September 2013 at three selected hospitals in North-Western Nigeria. Cases were patients diagnosed as having OF within the last 3years. Controls were randomly selected from patients (without OF) admitted to the maternity units of these hospitals. The odds ratio was used as a measure of association with their corresponding 95% confidence interval. Variables with p-value of <0.1 were included in the logistic regression model to generate adjusted Odds Ratios. Generally, the participants in the study perceived that cost of EmOC services was too expensive. Various socio-cultural and economic factors, including husbands' permission, use of traditional birth attendants, privacy, poor attitude of health care providers and poverty, cumulatively affected utilisation of EmOC services. Having Formal educational (OR; 0.013, CI; 0.001-0.530), Having Husband permission (OR; 0.028, CI; 0.001-0.664). Duration of labour ≥ 24hr (OR; 2.659, CI; 1.138-7.512), Delay in the decision to seek facility care (OR; 2.770, CI; 1.760-3.950), and Affordability of facility care cost (OR; 7.432, CI; 3.925-13.682).are risk factors for obstetric fistula. Health Education programs reaching out to both women and men with traditionally palatable messages that will change their attitudes and practices to take responsibility in reproductive health and empowerment of women can be a promising strategy to reduce the occurrence of obstetrics fistula. The government should strengthen the capacity of health facilities rendering EmOC through the provision of equipment, free drugs and services.